PENGARUH MEDIA GAMBAR SERI BERMUATAN MEDIA LOKAL TERHADAP KETERAMPILAN MENULIS KARANGAN DESKRIPSI DI KELAS V SD - Dimas Kusuma Wardhani; Yoyo Zakaria Ansori; Ujiati Cahyaningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study examines descriptive text writing skills using Picture Series Media with Local Cultural Content in fifth-grade elementary school students. The purpose of this research is to determine the difference in the effect of Picture Series Media on the ability to write descriptive texts among fifth-grade students. The research method applied was quantitative with a quasi-experimental design, specifically the Non-Equivalent Control Group Design. The research subjects consisted of 60 fifth- grade students of SDN Cigasong I, divided into two groups: class VA as the experimental group (30 students) and class VB as the control group (30 students). The research instruments included tests (pre-test and post-test), observations, interviews, and questionnaires. Data were analyzed through normality and homogeneity tests, Independent Sample T-Test, Paired Sample T-Test, and N-Gain test. The findings revealed that the data were normally distributed and homogeneous, thereby fulfilling the requirements for parametric testing. The mean post-test score of the experimental group was higher than that of the control group. The Paired Sample T-Test showed a significant difference between the pre-test and post-test results in the experimental group. Meanwhile, the N-Gain results indicated an average of 83.89% (high category) for the experimental group, whereas the control group achieved only 33.36% (medium category). Thus, it can be concluded that the use of Picture Series Media has a significant and effective influence in improving elementary school students’ descriptive writing skills.